Elderly health care in the Family Health Strategy and the prevalence of common mental disorders - Onofri Júnior,Venício Aurélio (2016)
The aims of the present study were to characterize the reasons for medical appointments and treatment procedures of elderly people in the Estratégia Saúde da Família ("Family Health Strategy") (ESF), with emphasis on mental health, as well as to identify the prevalence of common mental disorders, and compare this with the approaches described in medical records. A descriptive and cross-sectional study of 219 elderly persons was performed by reviewing medical records and applying a Self-Response Questionnaire (SRQ-20). For this population the average number of appointments per year was three, 42.3% of appointments were to obtain a medical prescription, and 70.9% of medical procedures involved the provision of medical prescriptions. There were eight referrals to specialized mental health services. The most prescribed psychiatric drugs were anxiolytics (55%), and antidepressants (29.7%). A total of 19.6% of the elderly persons had scores above seven in the SRQ-20. It was observed that a large proportion of mental disorders were not detected, and there was a failure in the procedures adopted. More investment in patient flow and the definition of assistance criteria for this population is required.